Decapentaplegic transcripts are localized along the dorsal-ventral axis of the Drosophila embryo. - St Johnston, R D (1987)
The decapentaplegic gene of Drosophila melanogaster (dpp) is related to the TGF-beta family of mammalian growth factors. In order to investigate the role of dpp during early development we examined the spatial pattern of expression of dpp transcripts in embryos. Transcription is first detected along the dorsal side of early syncytial blastoderm embryos. During germ band elongation, the gene is expressed in the region which will give rise to the dorsal epidermis. Since dppHin-embryos lack all derivatives of the dorsal epidermis, this suggests that dpp is required early in development for the determination of dorsal positional values. Later in embryogenesis, expression in the ectoderm changes to give two thin stripes running anterior-posteriorly along the length of the embryo. This pattern of expression may be involved in further subdivisions along the dorsal-ventral axis. At this stage, transcription can also be detected in discrete parts of the visceral mesoderm, foregut and hindgut.